Oculoectodermal syndrome is a mosaic RASopathy associated with KRAS alterations. (21st March 2015) - Peacock, Jacqueline D.; Dykema, Karl J.; Toriello, Helga V.; Mooney, Marie R.; Scholten, Donald J.; Winn, Mary E.; Borgman, Andrew; Duesbery, Nicholas S.; Hiemenga, Judith A.; Liu, Cong; Campbell, Stacey; Nickoloff, Brian P.; et al.
<x xml:space="preserve">Abstract</x> Oculoectodermal syndrome (OES) is a rare disease characterized by a combination of congenital scalp lesions and ocular dermoids, with additional manifestations including non‐ossifying fibromas and giant cell granulomas of the jaw occurring during the first decade of life. To identify the genetic etiology of OES, we conducted whole‐genome sequencing of several tissues in an affected individual. Comparison of DNA from a non‐ossifying fibroma to blood‐derived DNA allowed identification of a somatic missense alteration in KRAS NM_033360.3(KRAS):c.38G>A, resulting in p.Gly13Asp. This alteration was also observed in the patient's other affected tissues including the skin and muscle. Targeted sequencing in a second, unrelated OES patient identified an NM_033360.3(KRAS):c.57G>C, p.Leu19Phe alteration. Allelic frequencies fell below 40% in all tissues examined in both patients, suggesting that OES is a mosaic RAS‐related disorder, or RASopathy. The characteristic findings in OES, including scalp lesions, ocular dermoids, and benign tumors, are found in other mosaic and germline RASopathies. This discovery also broadens our understanding of the spectrum of phenotypes resulting from KRAS alterations. Future research into disease progression with regard to malignancy risk and investigation of RAS‐targeted therapies in OES is warranted. KRAS sequencing is clinically available and may also now improve OES diagnostic criteria. © 2015 Wiley Periodicals, Inc.